Differentiated Learning Process in the Independent Curriculum for the Subject of Islamic Religious Education - Nurmalia Nurmalia; Rizka Harfiani; Hasrian Rudi Setiawan (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to understand the process of designing instructional materials, implementing differentiated teaching strategies, and assessment in Islamic Religious Education. The study falls under the category of qualitative field research, focusing on investigating and describing the conditions or phenomena that occur in the field without manipulating variables. In this context, a descriptive approach is used to illustrate the processes of differentiated learning in the subject of Islamic Religious Education. The research was conducted during the second semester of the 2023-2024 academic year in February 2024. Data collection techniques included interviews, observations, and documentation. Data analysis involved data collection, reduction, display, and drawing/verifying conclusions. The findings indicate that differentiated learning in the independent curriculum for Islamic Religious Education at SD Negeri 106190 Kota Pari Pantai Cermin has been implemented successfully in accordance with the steps of differentiated learning. Firstly, teachers conducted Cognitive and Non-Cognitive Diagnostic Assessments to determine the readiness for learning as well as the interests, talents, and learning styles of each student. Secondly, teachers designed teaching modules tailored to the initial assessment results. Thirdly, teachers implemented differentiated teaching strategies through content, process, and product differentiation. Fourthly, teachers evaluated and reflected on the learning process. Through this differentiated learning approach, students become more active, creative, and innovative, finding learning more enjoyable. This helps to increase students' interest in learning, particularly in Islamic Religious Education, and assists them in becoming independent learners who appreciate diversity.